Effect Of Nifedipine On Fertility Of Male Lesser Bandicoot Rat (Bandicota Bengalensis) (Applied Biological Research, 2017)
Current study was designed to evaluate the antifertility effects of  nifedipine, a pharmaceutical medicament for high blood pressure.  Mature and healthy male lesser Bandicoot rats, Bandicota bengalensis Gray and Hardwicke, were fed on bait (cracked wheat, powdered sugar,  groundnut oil 98:2:2) containing 0.1 and 0.05% nifedipine for 12 days in  no-choice feeding test to record antifertility effects of nifedipine. The  factors studied were the effect on weight of reproductive organs, sperm  parameters in cauda epididymal fluid, breeding performance and histo morphology of testis. Nifedipine treatment significantly (P
Keywords: Antifertility effect; Bandicota bengalensis; histo morphology; nifedipine; sperm parameters